PENGARUH PENGETAHUAN WAJIB PAJAK, PENERAPAN E-FILING, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN ADMINISTRASI WAJIB PAJAK UMKM - Vinny Sherlina; Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims to determine the influence of taxpayer knowledge, the application of EFiling, and tax sanctions on UMKM taxpayer compliance. This research sampling method is a simple random sampling, with 100 sample of UMKM’s owner in Tangerang City. The data processing technique used in this study is a multiple linear regression model through IBM SPSS Statistic 25 Software . The results of this study indicate that taxpayer knowledge, the application of E-Filing, and tax sanctions have a positive effect on UMKM taxpayer compliance. The implication of this research is to provide additional benefits of knowledge, insight and information for readers about UMKM taxes.